Essence of values - Abd Razak, Dzulkifli (2010)
RECENTLY, I made a presentation entitled Reinventing Science at the Academy of Sciences Malaysia Inaugural Lectures. The crux of the talk was how Science, over the years, has become a mere tool of economic utility under the banner "commercialisation". In an era of knowledge economy, Science and Technology is the main vehicle for creating wealth to move up the value chain. The word "value" is now associated with "profitability" — the higher the value chain, the better it is for a company or individual. In other words, the meaning of "value" is narrowly understood in materialistic terms.